Hvorfor fortælle dig noget, du allerede ved? Om dufortællinger i dansk litteratur - Christensen, Pernille Meyer (Passage - Tidsskrift for litteratur og kritik, 2020)
Why Tell You Something You Already Know? – On Second Person Narratives in Danish Literature In this article, I propose a typology that expands the empirical field of second person narratives to include any narrative, fictional as well as autobiographical, where the “you” is designated, but not addressed. Based on the proposed typology, I investigate the development of second person narratives throughout Danish literary history; from experimental to conventionalized second person narratives.